Strengthening monitoring and evaluation to promote effective policy implementation in education sector of Somalia - JIMALE, Khadija Abdullahi (KDI School, 2021)
Implementation of education policies remains a challenge due to the lack of proper utilization of monitoring and evaluation (M&E) processes in the education. Effective monitoring of education is, therefore, crucial to ensure that education activities meet their aims and objectives in terms of quality and their ability to impact the desired knowledge. The study seeks to establish how strengthening M&E could promote effective policy implementation in the education sector of Somalia. It also evaluates how effective the current M&E system in the education sector in Somalia is for improving the implementation of education policies; identifies key factors, the problems and challenges facing the current M&E system and their causes, and suggests how to enhance the M&E system in education policy implementation. The study adapted a case study design and analytic framework to analyse and compare M&E systems used in education from five different countries. The study deliberately selected a cases of countries that have implemented successful and effective M&E systems. It used both primary and secondary data. Primary data were collected through interview guides which targeted Ministry of Education officials and other experts in the education sector. Secondary data was collected through desk reviews of selected countries that meet the criteria for selection. The study through qualitative comparative analyse (QCA) then examined patterns of similarities and differences across selected cases on M&E in the education. The research established there are no similarities between Somalia and most of the countries of South Africa in terms of M&E Models, however, the National government overs the M&E implementation across the country at different levels, in a country such as Uganda the National and District education offices ensures compliance with the ministry of education and sports norms and guidelines and educational performance that enables the collection of data at different levels of education management. The results amongst others indicated that the guidelines provided by policy documents in a country such as Rwanda are coordinated from the national levels, they also develop district education M&E plans, which are expected to be consistent with the strategic and policy priorities, outcomes, and outputs of the Education Sector Strategic Plan (ESSP) and M&E is conducted through Joint Annual Review. The data of the study also established that Somalia has also put in place policy guidelines designed to establish a system that puts in place common structures and standards across the education sector for tracking progress in the implementation of all Government education policies and programs which is similar to the case of Kenya. Based on the findings the ministry of education needs to establish a strong independent M&E division that handles all M&E activities, improve the coordination between education stakeholders and allocate an adequate budget it.
Thesis(Master) -- KDI School: Master of Public Policy, 2021
Keywords: Education and state--Somalia